"Enquanto seu lobo não vem": proposta de tradução para Libras no gênero contação de histórias infantis - Cruz, Lyvia de Araujo (2022)
The motivation for this research is my desire to present my reality, which is not the reality of every deaf person. I will talk about the importance of the Brazilian Sign Language (Libras) as a cultural identity factor for the Brazilian deaf community. According to IBGE, in Brazil there are more than 10 million deaf people, of which, considering the population over 5 years of age, only 22.4% know Libras. Faced with this difficult reality, which involves basic education, family, accessibility and language policies, which directly influence the life of people who depend on public policies to develop, have autonomy and occupy their space in society, my intention with this research is to propose a translation of a children’s book written in Portuguese into Libras, in the textual genre storytelling, which deeply explores Libras, valuing its visual-spatial characteristics, through this important sociolinguistic register for the literacy of deaf people, encouraging the appreciation of their identity and culture. To achieve the translation proposal, I trace a growing path, presenting research carried out on educational, cultural and translational aspects of Deaf Studies. Then, I trace a historical profile of the education of deaf children in Brazil. So, I approach deaf culture, specifically literature, when I deal with children’s literature, signed literature and deaf literature. I approach Translation Studies, in which I talk about the specifics of Intermodal Translation, more specifically about interpretation/translation strategies in Libras for children in the storytelling genre, valuing the grammar of sign language and its peculiar elements. I then present the translation proposal, which is the core of the work, making comments relating back to the theoretical framework.